Gating the conductance of extended metal atom chains: a computational analysis of Ru3(dpa)4(NCS)2 and [Ru3(npa)4(NCS)2]. Issue 27 (2nd July 2021) - Spivak, Mariano; de Graaf, Coen; Arcisauskaite, Vaida; López, Xavier
Abstract : The conductance of EMACs is tuned with the presence of electropositive/-negative atoms acting as gate electrodes by DFT calculations. Abstract : The effects of a gate potential on the conductance of two members of the EMAC family, Ru3 (dpa)4 (NCS)2 and its asymmetric analogue, [Ru3 (npa)4 (NCS)2 ] +, are explored with a density functional approach combined with non-equilibrium Green's functions. From a computational perspective, the inclusion of an electrochemical gate potential represents a significant challenge because the periodic treatment of the electrode surface resists the formation of charged species. However, it is possible to mimic the effects of the electrochemical gate by including a very electropositive or electronegative atom in the unit cell that will effectively reduce or oxidize the molecule under study. In this contribution we compare this approach to the more conventional application of a solid-state gate potential, and show that both generate broadly comparable results. For two extended metal atom chain (EMAC) compounds, Ru3 (dpa)4 (NCS)2 and [Ru3 (npa)4 (NCS)2 ], we show that the presence of a gate potential shifts the molecular energy levels in a predictable way relative to the Fermi level, with distinct peaks in the conductance trace emerging as these levels enter the bias window.